Perinatal and parental risk factors in an epidemiological study of children with autism spectrum disorder. (2nd April 2016) - Cassimos, Dimitrios C.; Syriopoulou-Delli, Christine K.; Tripsianis, Grigorios I.; Tsikoulas, Ioannis
Abstract : Objectives: This study examines several perinatal and parental risk factors in an epidemiological study of children with autism spectrum disorders (ASD). Methods: Based on a sample of 273 children with ASD who have been followed up at a General Hospital of North Greece, an additional sample of 273 healthy children, matched for age, is also recruited as a control group. Results: The innovative results indicate significant correlation of ASD with three critical categories of factors: genetic, perinatal, and environmental. According to the empirical findings of multivariate logistic regression analysis, critical factors indicating higher risk for autism disorders include: male gender; gestational age (GA); multiple gestations; maternal age at delivery; and, maternal education. Conclusions: The significant impact of perinatal and environmental factors can be indicative of their amplifying impact on genetic prone subjects.